SISTEM INFORMASI WARISAN BUDAYA TAKBENDA STUDI KASUS: BALAI PELESTARIAN NILAI BUDAYA (BPNB) JAWA BARAT - Pratama, William; Dewayani, Ery; Rusdi, Zyad (Jurnal Ilmu Komputer dan Sistem Informasi, 2020)
Application program "Intangible Cultural Heritage Information System Case Study: Balai Pelestarian Nilai Budaya (BPNB) West Java aims to complete the intangible cultural heritage data documentation system at the West Java Cultural Preservation Hall (BPNB) and help provide media for recording heritage data intangible culture. This application program uses the Rapid Application Development (RAD) method which is carried out in several stages, namely the planning phase, the analysis phase, the design phase, and the implementation phase. This application program uses several design tools, namely Flowcharts, Data Flow Diagrams, Entity Relationship Diagrams, Context Diagrams and Relationships Between Tables. This application program uses MySQL as a database, XAMPP as a link between the database and display, PHP as a programming language and display settings application Testing this application uses the Black Box Testing method and User Acceptance Test (UAT). Based on the trials conducted it can be concluded that the program created can be run and can assist users in completing the documentation of intangible cultural heritage data.